Antiviral activity of Hellenia speciosa (J. Koenig) S.R. Dutta rhizome metabolites against human adenovirus: insights from molecular docking and in vitro studies - Alnhhas, Sara; Bouback, Thamer; Albeshri, Abdulaziz; Alsahafi, Tasneem; Al-Sarraj, Faisal; Al-Sulaimany, Faten A.; Ali, Mohamed; Moatasim, Yassmin; Kutkat, Omnia; Gaballah, Mohamed; Badierah, Raied; Taibah, Eman O.; et al. (Frontiers in Pharmacology, 2026)
BackgroundHuman adenoviruses (HAdVs) cause a wide range of clinical diseases, yet effective antiviral therapies remain limited. Natural products, particularly medicinal plants, offer potential sources of antiviral agents.PurposeThis study aimed to evaluate the antiviral potential of Hellenia speciosa (J.Koenig) S.R.Dutta [syn. Costus speciosus (J.Koenig) Sm.; Costaceae] rhizome against HAdVs using both in vitro and in silico approaches.MethodsRhizome extracts were tested on Vero cells to assess cytotoxicity and antiviral activity. GC–MS identified bioactive metabolites, which were screened against adenoviral DNA polymerase using molecular docking.ResultsDocking predicted strong interactions of selected metabolites with the viral polymerase, guiding selection for in vitro assays. The methanolic extract exhibited low cytotoxicity and potent antiviral effects, while the ethanolic extract also showed notable activity. Selectivity indices indicated a favorable therapeutic window.ConclusionH. speciosa rhizome contains bioactivemetabolites with potential anti-adenoviral activity. While preliminary results are promising, further in vivo and clinical studies are required to confirm pharmacological relevance.